KINERJA BIDANG PEMBINAAN PELATIHAN DAN PRODUKTIFITAS DINAS TENAGA KERJA KOTA PEKANBARU TAHUN 2024 - Nababan, Steven Febrinaldo Richard; Hadi, Sofyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The general function of government is to regulate and protect the public, carry out government administration, provide services to the public, develop and build, and empower the community. One of the government affairs whose authority is delegated to the Regency or City is employment. In 2024, the Pekanbaru City Manpower Office was in the public spotlight. This was due to its performance being deemed suboptimal. One reason was a limited and untimely budget allocation, resulting in an inability to absorb the population of Pekanbaru City who wanted to participate in workforce training and certification programs. This study aims to analyze the performance of the Pekanbaru City Manpower Office in 2024, particularly in the areas of Training and Productivity Development. This study used a descriptive qualitative approach with data collection techniques including interviews, documentation, and literature review. The results of this study indicate that the performance of the Pekanbaru City Manpower Office in 2024 was suboptimal. Budget limitations and untimely budget allocations required the Manpower Office to delay payments to ensure the program continued. Furthermore, limited training infrastructure was also a factor preventing the Manpower Office from optimally absorbing the population who wanted to participate in workforce training and certification programs in 2024. Keywords: Performance, Productivity, Service Quality, Responsiveness, Responsibility, Accountability